(untitled) (Studia Prawnicze / The Legal Studies, 2008)
Generalną konstrukcją przypisywania określonemu podmiotowi skutków cudzych działań, polegających na stanowieniu, zmianie lub zniesieniu uprawnień i obowiązków we własnej sferze prawnej, jest konstrukcja reprezentacji. To dzięki niej istnieje możliwość skutecznego dokonywania działań w zastępstwie i dla innej osoby, choć, co oczywiste, kompetencja reprezentanta do działania wynikająca z tej konstrukcji prawnej wydaje się wtórna w stosunku do pierwotnej kompetencji reprezentowanego, przysługującej mu jako osobie, w której sferze prawnej realizują się lub mają się zrealizować skutki prawne danej aktywności. W sposób ogólny można zatem przyjąć, że z instytucją reprezentacji wiąże się możliwość wykonywania przez jakiś podmiot (reprezentanta) rozmaitych działań w imieniu innej osoby (reprezentowanego). Chodzi więc tu niewątpliwie o takie sytuacje, w których zamiast podmiotu uprawnienia udział w danej czynności bierze zupełnie inny podmiot. Reprezentacja jako konstrukcja prawna stanowi tym samym pewien mechanizm umożliwiający wywoływanie skutków prawnych w cudzej sferze prawnej przez zastąpienie przejawu woli reprezentowanego przejawem woli reprezentanta. Konsekwencją prawną jej zastosowania jest zatem niewątpliwie działanie samego reprezentowanego, co powoduje, że wszystkie skutki prawne takiego działania wystąpią (zrealizują się) nie w sferze prawnej reprezentanta, lecz w sferze wyłącznie zastąpionego. Wynikająca zaś stąd swego rodzaju tożsamość pomiędzy osobą, która dokonuje określonej czynności, a osobą, w której sferze prawnej mają powstać skutki tej czynności, jest konsekwencją występowania zasady autonomii woli podmiotów w kształtowaniu własnych stosunków prawnych, a zakres jej funkcjonowania dotyczy możliwości poszerzenia zakresu działania reprezentowanego, przejawiającego wolę występowania w obrocie prawnym przez reprezentanta. The subject of the presented deliberations is the legal construction giving the possibility to attribute a given subject with effects of other entities’ actions which actions consist of enactment, change, or abolishing of entitlements or obligations within own legal sphere-referred to as representation. Owing to such entitlement, the representative can act effectively on behalf of another person, even though, what is obvious, his competences arising from this legal construc tion seem to be secondary o the primary competence of repr is entitled to the representation, which he of given activities are realized or a person in whose legal sphere legal effects of given for are to be realized. Generally, one can assume that the institution of recents of representation is associated with the possibility to perform by a given subject a subject (the representative) various acts on behalf of another person (the represented). Representation as a legal construction constitutes, therefore, a mechanism, which makes it possible to cause legal effects in other entity’s legal sphere by substitu tion of the to f the represented manifestation of will with the manifestation of will of the representative. Legal consequences of its execution are, therefore, acts of the represented subject, and as a result all legal consequences of such acts will take place only in the legal sphere of the all le the represented. In order to cause legal effects via other persons, the subject of the legal sphere has at his disposal - within the structure of representation - certain legal instru ments, among which the most important is the institution of representation. The is legislator expresses this issue clearly. One may quote in this point Article 95(1) of the Civil Code, which allows-of course with stipulations specified by law arising from the nature of the legal act-to execute legal actions via a representa or tive. What it means is that, if a given person (representative) signs a declaration of will on behalf of another person (the represented) and at the same time executes a legal action which, as long as it is within the representative’s rights of acting on of the represented (authorisation), causes legal effects not for himself, but behalf of directly for the person represented by him. in the Polish legal system the source of competences authorising the represen In the tative to act can be either the will of the legislator or the will of the represented. Therefore, among the designata of the structure of representation, and according to Article 96 of the Civil Code, we can distinguish between statutory representation and proxy. Whenever the authorisation to act on behalf of the represented comes from his will, we are dealing with proxy. On the other hand, when the authorisa tion to execute legal actions on behalf of the represented arises as consequence of realization of an actual state, specified by provisions of law or a decision based on the provisions issued by court, or any administrative body therefore result ing from certain legal situations and independent of his will, we are dealing with statutory representation. Hence, we can assume that statutory representation has one common feature: the source of authorisation for the statutory representative is not a declaration of will of the represented. Differently, then, to proxy, statu tory representation is, in principle, imposed by law, because the will of the person for whom the representative shall be appointed has no influence on his choice, appointment or the scope of his authorisation (further functioning). A statutory representative is bound with a provision of law to represent a person, for whom he was appointed, which results in the situation, where any activities performed by him, regardless of the lack of will of the represented to act on his behalf, are executed on behalf f the represented person and with direct effect for this person enheme. The within her legal sphere. This means that appointing a representative of this kind should always take place according to the t e piace securing t interests. e represented person’s intere Basing on the present specific legal regulations, a wide group of subjects can Call be recognized statutory representatives. First of all we must point out, that a clas sic example are parents, having their parental authorities over minors (see Art. 98 of Family and Guardianship Code); carers who are obliged to take care of a minor (see Art. 155 (2) of FGC), or of a totally incapacitated who does not stay under parental authority (see Art. 13 (2) of the Civil Code); guardians appointed for the partially incapacitated (see Art. 16 (2) of the CC); temporary advisers ap pointed during the proceedings for incapacitation (see Art. 549 (2) of the Code of Civil Procedure); as well as heads of government offices, within the r meaning of provisions on employees of government offices, especially general directors of offices who who, basing on the provisions of Art 17 (1) of the Act of August, 8 1996 on the execution of State Treasury amended), who represent the State Competencies (Dz. U. No 106, item 493, as Treasury with reference to property they were entrusted with, as well as in the scope of the tasks of their offices, as specified by separate provisions- therefore they have statutory authorisation to represent the State Treasury. Additionally, within the statutory representation one can distin guish institutional representation - i.e. representation by a legally created organi sational body, which, as a whole is authorised to represent a given subject of civil law, within whose legal subjectivity he is operating acting outside on his behalf, and representation by an administrative body. The two above forms should be considered individual kinds of statutory representation. The presented examples of statutory representation, broadly analysed in this publication, show, that in the Polish legal system there are many subjects which, for various reasons and in the scope of execution of their own rights, are subject to competences of other persons appointed by the will of the legislator (either by virtue of law, or a provision issued by an administrative body)-their statutory representatives.